Kipper and the Giant Stage 6 - Hunt, Roderick (Oxford, United Kingdom Oxford University Press, 2012)
Kipper and the Giant follows the magical journey of Kipper, who, through a mystical (3z(Bmagic key,(3y (Bfinds himself in a village$1 (Band, in a twist, is mistaken for a giant. When the real giant causes chaos, Kipper helps mend the villagers' homes, shows kindness, and even tends to the injured giant. The story encourages themes of empathy, helpfulness, and understanding, showing that kindness bridges differences$1 (Bno matter your sizes